Preparation, Statistical Optimization and Characterization of Propolis-Loaded Solid Lipid Nanoparticles Using Box-Behnken Design - Sahar Taherzadeh; Atefeh Naeimifar; Ehsan Mehrabani Yeganeh; Zahra Esmaili; Reza Mahjoub; Hamid Akbari Javar (Tabriz University of Medical Sciences, 2021)
Purpose: Propolis is a resinous material obtained by honeybees with many biological and pharmacological properties which can be used for treatment of various diseases. Current study aims to formulate and characterize propolis-loaded solid lipid nanoparticles (SLNs) carrier system. Methods: The prepared SLNs, composed of glyceryl monostearate (GMS), Soy lecithin, Tween 80 and polyethylene glycol 400 (PEG 400), were fabricated employing solvent emulsification-evaporation technique. In addition, the impact of several variables including concentration ratios of GMS/Soy lecithin and PEG 400/Tween 80 along with emulsification time were evaluated on the size, polydispersity index (PDI) and zeta potential of particles. SLN formulations were optimized using Box-Behnken design. The particles were freeze dried and morphologically studied by scanning electron microscopy (SEM). The in-vitro release profile of propolis entrapped in the optimized nanoparticles was investigated. Results: The mean particle size, PDI, zeta potential, entrapment efficiency (EE) and loading efficiency (LE) of optimized propolis-loaded SLNs were found to be 122.6±22.36 nm, 0.28±0.06, -26.18±3.3 mV, 73.57±0.86% and 3.29±0.27%, respectively. SEM images exhibited nanoparticles to be non-aggregated and in spherical shape. The in-vitro release study showed prolonged release of propolis from nanoparticles. Conclusion: The results implied that the proposed way of SLN preparation could be considered as a proper method for production of propolis loaded colloidal carrier system.